Analisis Intensitas Hujan Provinsi Jawa Barat Tahun 2020 Menggunakan Association Rule Apriori dan FP-Growth - Bagus Almahenzar; Arie Wahyu Wijayanto (Universitas Pancasakti, 2022)
West Java is one of the areas in Indonesia with high rainfall. One of the causes of frequent flooding in the DKI Jakarta area is due to receiving water from the West Java area. The method used in this study is the Association Rule using the Apriori algorithm and FP-Growth. Association rule is a rule in data mining in determining all association rules that meet the minimum support (minsup) and minimum confidence (minconf) requirements in a dataset. In this study, the minimum support used is 5 and the minimum confidence is 0.9. The purpose of this study was to obtain a pattern of rainfall intensity that often occurs every month in the measurement station areas. The measurement stations in the West Java region are the Citeko Meteorological Station, the Penggung Meteorological Post, the Kertajati Meteorological Station, the Bogor Climatology Station, and the Bandung Geophysics Station. The results of this study indicate that in April, May, June, October, and November there is no pattern of rain intensity that occurs between the measurement station areas. Heavy, very heavy, and extreme rains are very rare. In July, August, and September, most areas do not experience rain.